Поглиблення енергетичної кризи як рушійна сила розвитку ринку енергозберігаючого інсталяційного устаткування - Косар, Н. С.; Пилипенко, В. М.; Кузьо, Н. Є. (Видавництво Львівської політехніки, 2015)
Обґрунтовано доцільність використання нетрадиційної енергетики, енергозбереження та енегоефективності в Україні. Встановлено, що найвищий потенціал розвитку в Україні належить вітровій та сонячній енергії. Визначено, що у приватному секторі будівництва ситуація з переходом на енергозберігаючі технології поступово набуває стабільно зростаючої тенденції та істотно залежить від розвитку ринку первинної нерухомості. Тому у роботі встановлена залежність попиту на первинну нерухомість від величини середньомісячної заробітної плати. Проаналізовано досвід використання енергозберігаючого інсталяційного устаткування у світі та в Україні, доцільність запровадження з цією метою державної підтримки. Встановлено, що сьогодні ринок України не відчуває нестачі у постачальниках інсталяційного устаткування. Проте фінансово-економічна криза призвела до того, що попит на закордонну продукцію преміум та середнього класу в Україні істотно знизився на користь дешевшого сегменту. Визначено, що у межах просування енергозберігаючого устаткування виробники та посередники мають дати змогу клієнту зрозуміти те, що від його закупівлі він не лише заощадить власні кошти в перспективі, але і отримає екологічну та соціальну вигоди, оскільки розумне використання енергозберігаючої та екологічної продукції робить внесок у розвиток суспільства, вирішення проблеми світової енергетичної кризи та у сталий розвиток загалом. Такі ідеї повинні знайти відображення у активізації заходів паблісіті та соціальної реклами усіх ланок галузевого ланцюга. The necessity of the use of alternative energy, energy saving and energy efficiency in Ukraine is substantiated. The experience in using of the alternative energy sources in the world and Ukraine is studied. The wind and solar energy are established to have the highest development potential in Ukraine. The development of energy obtaining methods also needs the development of the equipment that will efficiently use generated energy and therefore increase the final outcome in the resource saving. In these days, due to the rapid development of technologies, a variety of solutions and equipment that can provide a powerful reducing energy consumption exist, which consequently leads to cost and resource savings. The equipment and materials for the heating systems, water supply, sewerage installation have great demand, because they are a mandatory attribute in the construction or reconstruction of industrial, residential, administrative and public buildings these days. The heat pumps are appropriate items in the area of alternative energy sources. The rationalization of retaining pump systems and controls regulates the ratio of energy and water consumption. Air heat pumps allow to achieve the maximum use of renewable energy while working with other heating equipment, such as boiler or collector. Solar collectors are used to support heating systems and hot water even at sub-zero temperatures. Highly efficient vacuum heat sink can receive energy from both direct and diffused solar radiation. In order to improve the efficiency of the heating system one should also optimize the performance of heating devices -radiators and hydraulic or electric warmed floor and walls by operation of thermostats. It is determined that the situation with the transition to energy saving technologies in the private construction sector becomes more stable growing trend and essentially depends on the development of primary real estate market. Therefore, the dependence in the demand for primary property values is of the average wage. The experience of the use of energy-saving equipment installation in the world and in Ukraine is analyzed, the appropriateness of introducing to this end the government support. It is established that modern Ukrainian market as no shortage of suppliers of equipment installation that is classically divided into foreign and domestic. However, the financial crisis has caused the demand for foreign products the premium and middle class in Ukraine decreased significantly in favor of cheaper segment. It is determined that within the promotion of energy-saving equipment manufacturers and intermediaries should provide the client with the understanding that from his purchase, one not only saves their own funds in the future, but gains environmental and social benefits, as the clever use of energy saving and environmental products contributes to development society, to address the global energy crisis and sustainable development in general. These ideas should be reflected in the intensification of publicity measures and social advertising of all levels of the industry chain.
The deepening of the energy crisis as a driving force of market of the energy-saving installed equipment development
Keywords: installed equipment market; energy; energy-saving; energy efficiency; renewable energy; heating; water supply; public service ads; ринок інсталяційного устаткування; енергетика; енергозбереження; енергоефективність; відновлювальні джерела енергії; опалення; водопостачання; соціальна реклама